2012
DOI: 10.1080/09548963.2012.641775
|View full text |Cite
|
Sign up to set email alerts
|

Impact of place on museum participation

Abstract: This paper examines the impact of place on museum participation in England. For the first time in the cultural field, we use a multilevel logistic model to examine whether place matters after accounting for individual characteristics and area level compositional factors. Our findings show that the traditional social order remains intact, although other social cleavages have become important, and that significant variation exists in museum participation simultaneously at both the neighbourhood and local authori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 35 publications
4
40
0
2
Order By: Relevance
“…Whether gender is strongly associated with omnivorism depends upon the domain of activity selected for the analysis, as shown by the differentiated gender effects found in a number of studies (Van Eijck, 2001;Sintas and Alverez, 2002, Warde andGayo-Cal, 2009). Similarly, age effects have been contested, with some scholars suggesting that younger age cohorts are more inclined to be omnivores (Widdop and Cutts, 2012; Stichele and Laermans, 2006;Van Eijck, 2000), whilst others disagree (Warde et al, 2007;Warde and Gayo-Cal, 2009; Van Eijck et al, 2002).But apart from the odd study (Widdop and Cutts, 2012a), the existence of omnivores and other participation patterns in the sporting field have been under-researched. Moreover, if they resemble other cultural fields, what determines their existence remains a source of considerable debate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether gender is strongly associated with omnivorism depends upon the domain of activity selected for the analysis, as shown by the differentiated gender effects found in a number of studies (Van Eijck, 2001;Sintas and Alverez, 2002, Warde andGayo-Cal, 2009). Similarly, age effects have been contested, with some scholars suggesting that younger age cohorts are more inclined to be omnivores (Widdop and Cutts, 2012; Stichele and Laermans, 2006;Van Eijck, 2000), whilst others disagree (Warde et al, 2007;Warde and Gayo-Cal, 2009; Van Eijck et al, 2002).But apart from the odd study (Widdop and Cutts, 2012a), the existence of omnivores and other participation patterns in the sporting field have been under-researched. Moreover, if they resemble other cultural fields, what determines their existence remains a source of considerable debate.…”
mentioning
confidence: 99%
“…Similarly, age effects have been contested, with some scholars suggesting that younger age cohorts are more inclined to be omnivores (Widdop and Cutts, 2012;Stichele and Laermans, 2006;Van Eijck, 2000), whilst others disagree (Warde et al, 2007;Warde and Gayo-Cal, 2009;Van Eijck et al, 2002).…”
mentioning
confidence: 99%
“…Given that the libraries with the largest usage by members and greatest use by members from other catchment areas are also amongst the most attractive, and conversely those with the lowest usage are also ranked in the least attractive, we can conclude that this is a useful approach to understanding everyday cultural participation more generally. Thus, and echoing Widdop and Cutts (2012) in this study of libraries, we have demonstrated that location is an important factor for participation. In addition, though we have shown that the availability of everyday facilities surrounding a destination provides another important influence on participation.…”
Section: Resultsmentioning
confidence: 85%
“…In analysing the impact of location on participation, we are developing from a number of recent studies which have also sought to reveal the effects of supply and proximity on participation (e.g. Brook, 2013Brook, , 2016Hooper-Greenhill, Phillips, & Woodham, 2009;Widdop & Cutts, 2012). Brook (2013) demonstrates that geographic variables (in particular accessibility) used alongside socio-demographic variables are a better predictor of attendance at Opera venues in London than using socio-demographic variables alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation